2011
DOI: 10.1017/jfm.2011.188
|View full text |Cite
|
Sign up to set email alerts
|

Fokker–Planck model for computational studies of monatomic rarefied gas flows

Abstract: In this study, we propose a non-linear continuous stochastic velocity process for simulations of monatomic gas flows. The model equation is derived from a FokkerPlanck approximation of the Boltzmann equation. By introducing a cubic non-linear drift term, the model leads to the correct Prandtl number of 2/3 for monatomic gas, which is crucial to study heat transport phenomena. Moreover, a highly accurate scheme to evolve the computational particles in velocity-and physical space is devised. An important propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
99
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(99 citation statements)
references
References 32 publications
(23 reference statements)
0
99
0
Order By: Relevance
“…Gorji et al [32] reported very good agreement of their stochastic kinetic equation (44) with experiments for a slip/transition regime flow as did Bogomolov and Dorodnitsyn [10].…”
mentioning
confidence: 73%
See 2 more Smart Citations
“…Gorji et al [32] reported very good agreement of their stochastic kinetic equation (44) with experiments for a slip/transition regime flow as did Bogomolov and Dorodnitsyn [10].…”
mentioning
confidence: 73%
“…In [31,32], a kinetic equation is proposed that consists of replacing the Boltzmann collision integral with a velocity space stochastic operator. The proposed kinetic equation is written:…”
Section: The Spatial Scaling Problem From the Viewpoint Of A Kinetic mentioning
confidence: 99%
See 1 more Smart Citation
“…In these models, the gain part of the BCO is modelled by the Gauss, ellipsoidal Gauss, and Gauss-Hermite polynomials, while the loss part describes the exponential decay of the distribution function with a rate independent of molecular velocity. Recently, Gorji and co-workers have also proposed a model replacing the BCO by the Fokker-Planck collision operator (Gorji, Torrilhon & Jenny 2011;Gorji & Jenny 2013), which models the drift and diffusion in velocity space. Although this model is faster than the DSMC method near the continuum-fluid regime, for microflow simulations it suffers the same slowness as the DSMC method because of its particulate nature.…”
mentioning
confidence: 99%
“…Among recent developments in predicting these phenomena, Gallis and Torczynski [8] have presented a direct Monte Carlo simulation (DSMC). Gorji et al [9] obtained the mass flowrate by solving, numerically, a velocity-space stochastic equation addressing molecular motions. Veltzke and Thaming [10] pointed out that the mass flowrate in the slip flow regime can be accurately predicted by arguments of molecular spatial diffusion effects without using any fitting parameter.…”
Section: Introductionmentioning
confidence: 99%